Sustainable Construction Practices using Autoclaved Aerated Concrete (AAC) Blocks as a Replacement - Thakur Abhishek; Rao NV Surya Sarma Seshgiri; Raj Vijilius Helena; Saikumar A.; Sobti Rajeev; C Lavanya (E3S Web of Conferences)
Red bricks are the primary form of infill is extensively used in RCC structures. Blocks made of autoclaved aerated concrete have become a popular choice in construction industry. Autoclaved aerated concrete Blocks are prepared using lime, water and aerating agents mixed in a cement mixture. Cuboid blocks and prefabricated panels are the primary forms in which AAC is made. Concrete that has been made with a large number of closed air gaps is known as autoclaved aerated concrete. They have the ability to serve as replacements in the construction bricks as their strength is improved when compared with the traditional blocks. The AAC bricks are less dense, lightweight, long-lasting, and energy-efficient. make it, concrete is mixed with a foaming agent in moulds of varying sizes. Then, the resulting “cake lump” is wire- cut into blocks or panels, and steam is used to heat them. Autoclaving is the term for this procedure. The paper is focused on the exploration of these bricks as they are being collected from trash in industry, the substance is eco-friendly and composed of non-toxic components. The potential and sustainability of AAC blocks as a novel kind of building material have been examined in this paper. This paper offers a comparative cost analysis of red clay bricks and AAC blocks in addition to examining the viability and potential uses of AAC blocks in the construction industry